Rečevoj žanr komplimenta v sovremennoj rossijskoj kommunikacii - Voroncova, Tatʹâna А. (Stylistyka, 2019)
Unlike the majority of linguistic researchers, we consider the compliment as a speech genre, and a praise as a speech tactic of a positive assessment of the addressee. This tactic is the main and only speech tactic designed to serve the complimentary purpose, which expresses a positive attitude towards the interlocutor. Specifics of the compliment as a speech genre are defined by it possessing communicative independence and completeness. Unlike other genres of speech etiquette, the compliment is not attached to a certain situation and represents a facultative element of phatic communication. The etiquette essence of a compliment presupposes a certain convention of its contents, therefore theoretically it is supposed that the stated positive assessment shouldn’t be verified by the addressee. However, the importance of the category of sincerity for the Russian language consciousness determines the fact that in modern Russian communicative culture there is a special style of compliment which is caused by an aspiration of the sender to evoke trust of the interlocutor to the contents of a statement made. Markers of this style are various language emotional and estimated means and the structural-syntactic features particular to spontaneous informal conversation.